Pandangan Masyarakat terhadap Demokrasi Pemilu di Indonesia dengan Berlandaskan Pancasila dan UUD 1945 - Wati, Erni; Filosshophya, Filosshophya; Mubarok, Arif Rohman; Nurhasanah, Nurhasanah (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to find out the public's views on electoral democracy in Indonesia based on Pancasila and the 1945 Constitution. This research was conducted with a qualitative approach, through the literature review method. The main source of research data is research articles that are relevant to the focus of this article's problem and published through the google scholar website in the last 10 years. Data analysis was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The results of the analysis show that democracy includes social, economic, and cultural conditions that require free political liberation and provide an opportunity for the emergence of opinions of respect for the existence of people for participation in the life of the state, and to be respected by the community. Each country has its own characteristics in exercising public power or democracy. This is because the history of a country describes the culture, way of life, and desires to be achieved. The state has an obligation and authority to organize a democratic process based on the law and the basic principles of democracy. It is important to restore democratic life based on laws based on Pancasila values